An Approach Based on Langranian Relaxation and the Taboo Search for the MultiStage Lot Sizing Problem. - Oliveira, Lilian Kátia de; Berretta, Regina (Revista Gestão da Produção Operações e Sistemas, 2007)
This paper addresses the multistage capacitated lot-sizing problem. The objective is to determine the quantity to be produced in order to attain the demand xx in each period of a planning horizon. The aim is to minimize production, inventory and setup costs. The resources are limited and the setup times are considered. The formulation presented is a mixed integer programming and the problem is NP-Hard. The heuristics use Lagrange relaxation and Tabu Search and they are compared with the ones in França et al. (1997), Tempelmeier and Derstroff (1996) and Özdamar and Barbarosoglu (2000). Keywords: Lot-Sizing, Lagrangean Relaxation, Tabu Search.